IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI MEDIA PEMBELAJARAN SEJARAH LOKAL RUMAH ADAT MELAYU PALEMBANG DI SMA AISYIYAH 1 PALEMBANG - Dewi Setyawati; Heryati Heryati; Indianis Ivada (Raudhah - Proud To Be Professional, 2024)
This research was motivated by the lack of local history-based media implemented by teachers in schools. The research aims to determine the Implementation of Character Education using Local History Media of Palembang Malay Traditional Houses at SMA Aisyiyah 1 Palembang. The data collection method in this research uses observation, interviews and documentation methods which are then descriptive qualitative. This research uses sociology, education, anthropology and geography approaches. The results of this research are 1. Aisyiyah 1 Palembang High School students' understanding of local history is good. Students are able to explain the meaning of local history, know the local history in the city of Palembang. describing the existing local history, to the point of adopting the values ​​and wisdom contained in local history. Then it also describes the philosophical value of the local history of the Palembang Malay Traditional House. 2) Implementation of this character education by means of the teacher first preparing a learning implementation plan (RPP) and syllabus, as well as Media Banners and Miniatures of Palembang Malay Traditional Houses, then in the RPP and teacher syllabus in each material the teacher always embeds character education in the Philosophical Values ​​of Traditional Houses Malay through a learning process starting from initial learning activities, core learning activities, closing learning activities, and evaluation. 3) Inhibiting and Supporting Factors faced by teachers and students in the Implementation of Character Education through Learning Media Local History of Palembang Malay Traditional Houses at SMA Aisyiyah 1 Palembang, namely, the inhibiting factors are time, media, environment and learning models that are not implemented enough. Supporting factors are facilities and infrastructure as well as social media that support character education 4. Students' perceptions regarding the Implementation of Character Education through Learning Media Local History of the Palembang Malay Traditional House at SMA Aisyiyah 1 Palembang Implementation of Character Education for the Palembang Malay Traditional House at SMA Aisyiyah 1 Palembang has been carried out successfully. good, because it is proven that the character of the students shows good morals during the learning process, this is also supported because of the strict rules applied by the school regarding discipline and habituation.